Pesan Dakwah dalam Novel Athirah - Nina Herlina; Dang Eif Saiful Amin; Rohmanur Aziz (Tabligh: Jurnal Komunikasi dan Penyiaran Islam, 2019)
ABSTRACTThis paper aims to determine how the macro-structure of the novel Athirah propaganda message, superstructure message Athirah propaganda in the novel, and the microstructure of propaganda messages in the novel Athirah Endah Alberthiene work. The research method using the method of discourse analysis approach is qualitative, in discourse analysis Teun A. Van Dijk models is researching on the search for the macro-structure of thematic text. while the superstructure is discussed in the schematic, and the microstructure of the text that is in terms of semantic, syntactic, stylistic and rhetorical. The results showed that in the structure of the macro in this novel are arranged in the theme of patience, and a woman named Athirah toughness in the face of life's trials. In the superstructure Alberthiene Endah make this novel with the flow back and forth, there are grooves that tell of the past, but still easily understood by the reader. While the microstructure Alberthiene Endah using language that is quite extensive and figurative language or imagery. Tenses used mostly using active voice form. ABSTRAKTulisan ini bertujuan untuk mengetahui bagaimana struktur makro pesan dakwah dalam novel Athirah, Superstruktur pesan dakwah dalam novel Athirah, dan struktur mikro pesan dakwah dalam novel Athirah karya Alberthiene Endah. Metode penelitian menggunakan metode pendekatan analisis wacana bersifat kualitatif, Dalam analisis wacana model Teun A. Van Dijk ini meneliti tentang mencari struktur makro teks tentang tematik. sedangkan superstruktur dibahas dalam skematik, dan struktur mikro teks yaitu dari segi semantik, sintaksis, stilistik dan retoris. Hasil penelitian menunjukan yaitu secara struktur makro dalam novel ini disusun dalam tema kesabaran, dan ketangguhan seorang perempuan bernama Athirah dalam menghadapi cobaan hidup. Secara superstruktur Alberthiene Endah membuat novel ini dengan alur maju mundur, ada alur yang menceritakan masa lampau, namun tetap mudah dimengerti oleh pembaca. Sedangkan secara struktur mikro Alberthiene Endah menggunakan bahasa yang cukup luas dan bahasa kiasan atau perumpamaan. Bentuk kalimat yang digunakan kebanyakan menggunakan bentuk kalimat aktif.